The computer as prosthesis - Reflections on the use of a metaphor - Mey, Jacob L. (HERMES - Journal of Language and Communication in Business, 2000)
The use of metaphors in a computerized setting is not without its problems. Far from being a simple ‘tool’, in the ordinary sense, the computer has a built-in propensity for ‘capturing’ both its maker and its users. One could say that by its very structure, it defies the boundaries set for normal human activity: speed, memory, (co-) presence, interacting, steering, producing, and so on. If we talk about the computer as a ‘pros-thesis’ (one of the most recent metaphors that have been suggested), such talk too, implies a certain attitude towards the prosthetic ‘tool’ The present article examines the various aspects of this particular metaphor and discusses its pros and cons, also with a view towards the newly emerging sub-discipline of Cognitive Technology, CT.